2016
DOI: 10.1371/journal.pone.0160786
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Neuropathic Pain Leads to a Hyporesponsive Barrel Cortex with Enhanced Structural Synaptic Plasticity

Abstract: Chronic pain is a long-lasting debilitating condition that is particularly difficult to treat due to the lack of identified underlying mechanisms. Although several key contributing processes have been described at the level of the spinal cord, very few studies have investigated the supraspinal mechanisms underlying chronic pain. Using a combination of approaches (cortical intrinsic imaging, immunohistochemical and behavioural analysis), our study aimed to decipher the nature of functional and structural change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 89 publications
1
10
1
Order By: Relevance
“…The authors showed that long-lasting orofacial neuropathic pain is associated with exacerbated neuronal activity and synaptic plasticity at the cortical level. Our results showing higher Piccolo immunoreactivity in the TBSC regions in chronic DED animals are in accordance with those of the aforementioned study [37]. Thus, the increase of Piccolo staining strongly indicates that profound synaptic reorganization occurs with DED.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The authors showed that long-lasting orofacial neuropathic pain is associated with exacerbated neuronal activity and synaptic plasticity at the cortical level. Our results showing higher Piccolo immunoreactivity in the TBSC regions in chronic DED animals are in accordance with those of the aforementioned study [37]. Thus, the increase of Piccolo staining strongly indicates that profound synaptic reorganization occurs with DED.…”
Section: Discussionsupporting
confidence: 93%
“…Accumulating evidence has suggested that chronic changes of activity in primary afferent neurons induce synaptic adaptations in the central nervous system and lead to functional remodeling of presynaptic sites [37]. Piccolo is one of the components of the presynaptic zone shown to be involved in synaptic plasticity [38].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have proved that plastic changes of various brain regions concerning pain processing contributed to the recovery of neuropathic pain. Those regions mainly involved the prefrontal-limbic-brainstem areas, the somatosensory cortices, the prefrontal cortex (PC) [7], the insular cortex (IC), the anterior cingulate cortex (ACC) [8], the basal ganglion regions, the hypothalamus (HT), and the ventral midbrain (VMB) [9, 10]. All of these changes were considered a maladaptive response of noxious damage by increased activation and reduced functional connectivity of subcortical pathways, which were believed to contribute to the increased pain sensitivity [11, 12].…”
Section: Introductionmentioning
confidence: 99%